A Meta-Analysis of the Effects of Secondhand Smoke Exposure toward the Incidence of Pneumonia in Children Under Five - Maya Ayu Riestiyowati; Setyo Sri Rahardjo; Bhisma Murti (Journal of Epidemiology and Public Health, 2020)
Background: Pneumonia is an acute respira